2004
DOI: 10.1111/j.1472-8206.2004.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Is it important to correct apparent drug tissue concentrations for blood contamination in the dog?

Abstract: The goal of this study was to quantify in the dog the error that is made in assessing drug tissue concentrations when no correction for blood contamination is performed and hence to determine in which organs such a correction should be made. The organs investigated were the heart, the brain, the liver and the skeletal muscle, and the test drug used was the H1-antihistamine, cetirizine (0.1 or 0.6 mg/kg/day for 3 days, orally, n = 6 dogs). Radiolabelled serum albumin was used to quantitate blood trapped in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Additionally, others [17] have suggested that no correction of apparent drug tissue concentrations for blood contamination was necessary for brain tissue, unless the brain-to-plasma ratio is below 0.1. The pharmacokinetic parameters Tmax (the time to reach peak concentration) and Cmax (the peak concentration) were thus calculated accordingly by non-compartmental analysis of mean concentration time data with WinNonlin (version 5.2, Pharsight, Mountain View, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, others [17] have suggested that no correction of apparent drug tissue concentrations for blood contamination was necessary for brain tissue, unless the brain-to-plasma ratio is below 0.1. The pharmacokinetic parameters Tmax (the time to reach peak concentration) and Cmax (the peak concentration) were thus calculated accordingly by non-compartmental analysis of mean concentration time data with WinNonlin (version 5.2, Pharsight, Mountain View, CA).…”
Section: Methodsmentioning
confidence: 99%
“…One potential confounding factor associated with the tissue/blood concentration ratio is the possibility of residual blood trapped in the tumor. However, because temsirolimus tissue concentration is greater than its ng/g blood concentration (mean tissue concentration of 220 ng/g versus mean whole blood concentration of 174 ng/mL) and its volume of distribution (533-699 L) is much greater than blood volume (6 L), the correction of tissue concentration for blood contamination is theoretically unnecessary (16). Correlative analyses of the tumor tissue (pending) for the inhibition of the key regulators (p70 S6 kinase, eIF4E, PTEN, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Blood contamination is another consideration as a source of variability in tissue concentrations, particularly for FNA samples, for which forceful suction is applied to a small yet very-well-perfused mass (21,27,28). In a study that investigated the error associated with blood contamination in measuring liver tissue drug concentrations in dogs, measurements were slightly underestimated if they were not corrected for residual blood (28).…”
Section: Discussionmentioning
confidence: 99%
“…In a study that investigated the error associated with blood contamination in measuring liver tissue drug concentrations in dogs, measurements were slightly underestimated if they were not corrected for residual blood (28). Correction of tissue concentrations for blood contamination is less of a concern for compounds with high tissue-to-plasma ratios, such as paritaprevir and ritonavir.…”
Section: Discussionmentioning
confidence: 99%